The Effect of Retribution for Tourism Objects and Number of Tourist Attractions on Regional Original Income in North Tapanuli Regency in 205-2019 - Handoko (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2021)
This study aims to determine the effect of the number of restaurants/restaurants/cafes, regional levies and the number of tourist visits on the local revenue of North Tapanuli Regency. This type of research is quantitative research. The population of this study is the 2015-2020 PAD Report and North Tapanuli in Figures. The research sample is data on reports on the number of restaurants/restaurants/cafes, regional levies and the number of tourist visits from 2015-2020. The data of this research are secondary data. Hypothesis testing in this study using multiple linear regression analysis with SPSS program. Based on the results of the study, it can be concluded that the number of tourist visits, the number of tourist objects and tourist fees have an influence on local revenue.